If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 5y + 2 = 0 Reorder the terms: 2 + -2x + 5y = 0 Solving 2 + -2x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2x + -2 + 5y = 0 + -2 Reorder the terms: 2 + -2 + -2x + 5y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2x + 5y = 0 + -2 -2x + 5y = 0 + -2 Combine like terms: 0 + -2 = -2 -2x + 5y = -2 Add '-5y' to each side of the equation. -2x + 5y + -5y = -2 + -5y Combine like terms: 5y + -5y = 0 -2x + 0 = -2 + -5y -2x = -2 + -5y Divide each side by '-2'. x = 1 + 2.5y Simplifying x = 1 + 2.5y
| 3xa=5xa+40 | | 8r+4=8 | | 5(2x-8)-2(x+2)-16x= | | 6x-5y-12=0 | | 3x+y=-36 | | 4-x/x+2sqrtx | | 29/24-7/8 | | (y-x-1)dx+(x+y-1)dy=0I | | 7u-16u=0 | | -2,-8=1/2 | | (-2,_8);m=-1/2 | | 11x(13/19) | | (6x)(24)=72 | | 13/19=x/11 | | 103/7x101/2= | | 103/7*101/2 | | 14+5=25 | | 14+5=25 | | 103/7x101/2 | | 5x+200=2x+100 | | 17/12-(1/8 | | 8y^7-12y^5/2y^3= | | 4n-6=5-2n | | -9+n4=-7 | | 8y^7-12y^5/2y^3 | | (x/(x-3))+(4/x) | | (x/x-3)+(4/x) | | 6x^5-4x^3=-1 | | 3x+6y+5-y-9x-7= | | 5(x-5y)=0 | | (1/7)^(2x-5)=49 | | 29x+5=4.7x-7.6 |